Internecine War Killings - Fabre, C (2012)
In his recent book Killing in War, McMahan develops a powerful argument for the view that soldiers on opposite sides of a conflict are not morally on a par once the war has started: whether they have the right to kill depends on the justness of their war. In line with just war theory in general, McMahan scrutinizes the ethics of killing the enemy. In this article, I accept McMahan's account, but bring it to bear on the entirely neglected, but nevertheless interesting, issue of what the military call 'blue-on-blue' killings or, as I refer to such acts here, internecine war killings. I focus on the case of the soldier who is ordered by his officer, at gunpoint, to go into action or to kill innocent civilians, and who kills his officer in self-defence. I argue that, at the bar of McMahan's account of the right to kill in self-defence, the officer lacks a justification for attacking the soldier as a means of enforcing his order, and the soldier thus sometimes (but not always) has the right to kill his officer should the latter so act. © 2012 Cambridge University Press.